Development of a Fitness Report Using the AppSheet Platform for Elementary School Students - Kusumawardhani, Delvya Intan; Indahwati, Nanik; Taringan, Christof Advanta; Fikri, Muhammad Dzul (Universitas Negeri Surabaya, 2024)
Purpose: This research aims to enhance the monitoring and reporting of physical fitness among elementary school students by developing an online fitness report application based on AppSheet. Materials and Methods: The methods employed include data collection and organization, application development, testing, and adjustments. This application utilizes Google Spreadsheet as its primary database, enabling real-time access for teachers, students, and parents. Result: Research findings indicate that the application is effective and efficient in monitoring students' physical fitness, thereby increasing engagement among all stakeholders. Testing with 35 teachers revealed some issues, such as app crashes due to re-registration, which were subsequently addressed through coding adjustments. Conclusion: The conclusion drawn from this research is that the application successfully develops an innovative and practical technological solution for monitoring the physical fitness of elementary school students. Despite the reliance on stable internet connectivity, mitigation steps such as offline data storage, user training, feature enhancement, data security improvements, periodic evaluation, collaboration with fitness experts, and testing in various conditions are recommended to ensure consistent data availability and optimize the application's usage.